2017
DOI: 10.1186/s12885-017-3772-9
|View full text |Cite
|
Sign up to set email alerts
|

Does anthracycline-based chemotherapy in pregnant women with cancer offer safe cardiac and neurodevelopmental outcomes for the developing fetus?

Abstract: BackgroundCancer treatment during pregnancy is a growing problem especially now that women delay childbearing. Systemic treatment of these malignancies during pregnancy centers mainly on the anticancer drugs anthracyclines, widely used in treating hematological and breast cancer during pregnancy and sometimes associated with early and late toxicity for the fetus. Owing to concern about their cardiac and neurodevelopmental toxicity more information is needed on which anthracycline to prefer and whether they can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 78 publications
0
17
0
2
Order By: Relevance
“…A meta-analysis by Song et al including 39 studies published between 1997 and 2018 demonstrated that neoadjuvant platinum-based chemotherapy was a good option to manage uterine cervical cancer during the second and third trimesters [23]. In the same way, several studies have shown the good prognosis of children exposed to anthracyclines during pregnancy [24][25][26] although this regimen raises concerns about fetal cardiac toxicity [27]. Similarly, taxanes can also be used after the first trimester of pregnancy [28].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Song et al including 39 studies published between 1997 and 2018 demonstrated that neoadjuvant platinum-based chemotherapy was a good option to manage uterine cervical cancer during the second and third trimesters [23]. In the same way, several studies have shown the good prognosis of children exposed to anthracyclines during pregnancy [24][25][26] although this regimen raises concerns about fetal cardiac toxicity [27]. Similarly, taxanes can also be used after the first trimester of pregnancy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some anthracyclines, such as doxorubicin and daunorubicin are safer during pregnancy. Idarubicin is more lipophilic and has an increased risk of crossing the placenta with a higher rate of potential fetal complications than the other anthracyclines [17, 18]. Therefore, idarubicin should be avoided during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents most commonly used in pregnancy are anthracyclines and alkylating agents. Furthermore, the use of the FAC regimen (5FU, Doxorubicin, Cyclophosphamide) appears to be associated with a low risk of complications and fetal malformations when administered in the 2 nd and 3 rd trimesters of pregnancy [4,37].…”
Section: Surgerymentioning
confidence: 99%